STRATEGI PENGELOLAAN PROGRAM PERHUTANAN SOSIAL DI KESATUAN PENGELOLAAN HUTAN LINDUNG SENGAYAM - Rino, Rino; Aryadi, Mahrus; Abidin, Zainal (Lambung Mangkurat University-Indonesia, 2025)
Centralized forest management in Indonesia has ultimately resulted in failure in maintaining the sustainability of forest functions (experiencing deforestation) and the balance of the ecosystem within it. It is necessary to formulate policies regarding forest governance and forest management plans and appropriate forest utilization. The research was carried out at the Sengayam Protected Forest Management Unit (KPHL). Based on the determination of the work areas for Community Forests and Village Forests in the Sengayam Protected Forest Management Unit, namely KTH Tampuk Cipta Sejahtera and KTH Batuah in Batuah Village, West Pamukan District, Kotabaru Regency. This research was conducted from March 31 2023 to June 31 2023. The method used in this research was purposive sampling, calculated using questionnaire results, recommended from field interviews, spatial analysis and SWOT analysis. The results of the research are that utilizing the availability of large enough land as a strategic location for the management of the Social Forestry Program in KPHL Sengayam, land use and protection efforts for sengon, areca nut and cocoa plants as well as vegetable and fruit plants will improve the local regional economy as well as NTFPs for kelulut honey, opening access to information for marketing the production of each KTH by utilizing community and government support to disseminate information and access, there needs to be more empowerment for communities around the forest and more involvement in their role so that instant thinking patterns can be changed from looking for land for settlement to more on forest conservation, increasing farmers' interest in managing Hkm and HD by explaining the benefits they can gain from managing Hkm and Village Forests through the Social Forestry Program at KPHL Sengayam.